DISTRIBUSI NILAI TAMBAH BERAS ORGANIK DENGAN PENDEKATAN KONSEP RANTAI NILAI - Harnadi, Regina Vrischika; Ambarawati, I Gusti Agung Ayu; Suryawardani, I Gusti Ayu Oka (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management), 2019)
ABSTRACT Consumer awareness on food safety and organic product consumption has open up an opportunity for producers of organic products. The Somya Pertiwi Farmer Group is one of the organic rice cultivator that has been certified by LeSos. The purpose of this study is to analyze the flow of actors, products, financial, and information, as well as the distribution of value added in the value chain of organic rice agribusiness produce by Somya Pertiwi. This research was conducted along the value chain using forward and backward approach from the focus point of the research which is the Somya Pertiwi Farmer Group. The research shows that the actors’ flow devided by main and supporting actors. The product flows from upstream to downstream shows the transformation of 43,900 kg of dried organic red rice grain become 20,852 kg of organic red rice and 76,700 kg of dry organic white rice grain become 36,432 kg of organic white rice. The flow of information moves both from upstream, downstream, as well as from supporting institutions such as the Somya Pertiwi Farmer Group, LeSos, and also the Internal Control System. The most balanced value-added distribution is in the organic red rice value chain through UD Sari Bulan Utama with 41%-46% added value at the farmer level, 20%-23% at the processing unit, 19%-22% at the wholesaler level, and 9%-19% at the reseller level. Increase in the percentage of sales at the farmer level to increase farmers’ income. Processing unit can increase organic white rice value added by increasing the retail price. Government need to establish supervision at the wholesaler and retailer level.